Association of N, N-diethyl-m-toluamide (DEET) with arthritis among adult participants. - Taihong Lv; Hanming Yu; Zishuo Ji; Yuru Chen; Qi Zhao; Li Ma (PLoS ONE)
Background N, N-diethyl-m-toluamide (DEET), an active ingredient prevalent in insect repellents, has its effects on human health under ongoing debate and scrutiny. Objective This study aimed to investigate the association between exposure to DEET and arthritis outcomes within the broader adult demographic, leveraging data obtained from the National Health and Nutrition Examination Survey (NHANES). Methods 3-diethyl-carbamoyl benzoic acid (DCBA) was used as a specific indicator of DEET exposure. Drawing on NHANES 2007-2016 data, our study incorporated 7065 adults to examine urinary DCBA impacts on arthritis risks using logistic regression and cubic spline analysis. Results Our study included a total of 7065 patients, of which 1860 (26.33%) had arthritis. After adjusting for all covariates, the multivariate logistic regression analysis showed that high DCBA levels (>7.37 ug/L) were associated with an increased likelihood of arthritis (OR: 1.236, 95% CI: 1.037-1.474, p = 0.018). Nevertheless, participants in the highest quartile of DCBA levels (Q4) were associated with a 33.9% decreased risk of rheumatoid arthritis (OR: 0.661; 95% CI: 0.501-0.872; p = 0.003). Conclusion It was observed that increased levels of DCBA are positively associated with the prevalence of arthritis in the adult population. Conversely, high concentrations of DCBA showed a reverse correlation with the prevalence of rheumatoid arthritis.